Post Covid-19 Complications of Symptomatic and Asymptomatic Among Healthcare Professionals Working in Tertiary Care Hospital of Lahore Pakistan - Ayesha Anayat, Maryam Naz, Sohail Amjad, Hamza Tanveer, Fakhra Fakhr, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Growing evidence shows that a significant number of patients with COVID-19 experience prolonged symptoms, known as Long COVID. COVID-19, caused by SARS-CoV-2, can involve sequelae that last weeks to months after initial recovery. The objective of this study is to assessing the long-term effects of COVID-19 and estimate the prevalence of each symptom of patients at a post-COVID-19 stage. Aim: This study was conducted to determine the frequency of post COVID effects among symptomatic and asymptomatic patients at a tertiary hospital Lahore, Pakistan. Materials and Methods: This cross-sectional study was conducted among the population (such as doctors, nurses, paramedical staff, students and faculty) at a tertiary hospital Lahore, Pakistan. This study included 30 participants and the collected data had been checked, coded, entered and exported at SPSS version 25 for analysis. Pearson chi square test was used for the statistical analysis of the data. Results: Among 30 participants, no one show symptoms of hypertension, diabetes mellitus and visual problems during COVID-19 and after recovery.8 patients were asymptomatic and 22patients were symptomatic which shows post COVID effects such as which include dyspnea (67.7%), mental confusion (26.7%), tiredness (93%), chest pain (16.7%), anorexia(26%), insomnia(26%), dyspepsia(67%), headache(66.7%), fatigue(50%), fever(10%), loss of smell(33%), weakness(40%), hypoxia on altitude(60%), breathlessness(70%), arthrgia(13.3%), mental confusion(26.7%), post-exertinal malasia(16.7%), sore throat(10%), joint pain(40%) Conclusion: Conclusion based on the study result that most common post-COVID long terms effects are dyspnea, weight loss, mental confusion, anorexia, arthrgia, post-exertinal malsiae, insomnia, fever, hypoxia, breathlessness, sore throat. Symptoms can be controlled by taking proper precautionary measure and strict following on PPE. The problem can only get worse with time if not followed PPE